Causal effect of the Tokyo 2020 Olympic and Paralympic Games on the number of COVID-19 cases under COVID-19 pandemic: An ecological study using the synthetic control method - Yamamoto, N.; Mitsuhashi, T.; Tsuchihashi, Y.; Yorifuji, T. (Journal of Personalized Medicine, 2022)
Previous studies have not assessed the causal effect of the Olympic Games on the spread of pandemics. Using the synthetic control method and the national public city data in Japan recorded from February to September 2021, we estimated the causal effects of the Tokyo 2020 Olympic and Paralympic Games on the number of coronavirus disease 2019 (COVID-19) cases. The difference between the number of COVID-19 cases in Tokyo and a counterfactual "synthetic Tokyo" (created using synthetic control method) after the opening of the Tokyo 2020 Games (23 July 2021) widened gradually and then considerably over time. It was predicted that the Tokyo 2020 Games increased the number of COVID-19 cases in Tokyo by approximately 469.4 per 100,000 population from the opening of the event to 30 September. However, sensitivity analysis of the ratio of the pre- and post-game root mean square prediction errors using regression weights did not suggest robustness. Our results showed that the Tokyo 2020 Games probably increased the number of COVID-19 cases even under preventive regulations; however, the extent of this increase was difficult to estimate clearly due to an overlap with the fifth wave associated with the Delta variant.